Pediatric patients with bicytopenia/pancytopenia: Review of etiologies and clinico-hematological profile at a tertiary center - Shano Naseem; Neelam Varma; Reena Das; Jasmina Ahluwalia; Man Updesh Singh Sachdeva; Ram Kumar Marwaha (Wolters Kluwer Medknow Publications, 2011)
Background: The etiology of bicytopenia/pancytopenia varies widely in children, ranging from transient marrow viral suppression to marrow infiltration by fatal malignancy. Depending on the etiology, the clinical presentation can be with fever, pallor or infection. Knowing the exact etiology is important for specific treatment and prognostication. Aims: To evaluate the etiological and clinico-hematological profile in children with bicytopenia and pancytopenia. Materials and Methods: A review of bicytopenic and pancytopenic children referred for bone marrow examination from January 2007 to December 2008 was done. Detailed history, clinical examination and hematological parameters at presentation were recorded. Results and Conclusion: During the study period, a total of 990 children were referred for bone marrow examination for different indications. Of these, 571 (57.7%) had either pancytopenia (17.7%) or bicytopenia (40%). Commonest form of bicytopenia was anemia and thrombocytopenia seen in 77.5% cases, followed by anemia and leukopenia in 17.3% and leukopenia and thrombocytopenia in 5.5% cases. Most common etiology was acute leukemia (66.9%) in bicytopenic children and aplastic anemia (33.8%) in pancytopenic children. Children with bicytopenia had a higher incidence of underlying malignancy (69.5% vs. 26.6%), splenomegaly (60.5% vs. 37.4%), lymphadenopathy (41.8% vs. 15.1%) and circulating blasts (64.6% vs. 20.1%) and a lower incidence of bleeding manifestations (12.1% vs. 26.6%) as compared to children with pancytopenia.